Activation of the neurokinin-1 receptor by substance P triggers the release of substance P from cultured adult rat dorsal root ganglion neurons - Arihiro Koji; Li Yu-Sang; Tang He-Bin; Nakata Yoshihiro (Molecular Pain, 2007)
Abstract Background Although substance P (SP) is an important primary afferent modulator in nociceptive processes, it is unclear whether SP regulates its own release from primary sensory neurons. Results Using a highly sensitive radioimmunoassay for SP, we have demonstrated that the activation of neurokinin-1 receptor by SP or GR73632 (a potent neurokinin-1 receptor agonist) triggered an increase of SP release from cultured adult rat dorsal root ganglion (DRG) neurons depending on the dose and exposure time within 60 min, and thereafter, the SP release level gradually decreased over 360 min. Accompanying the SP release, a significant reduction in the percentage of neurons expressing neurokinin-1 receptor on their membranes during exposure to SP (200 pg/dish) occurred time dependently (56 ± 5% and 32 ± 2% at 180 and 360 min, respectively). The GR73632-evoked (10 nM, 60 min) SP release was attenuated by several inhibitors for mitogen-activated protein kinase kinase, p38 mitogen-activated protein (MAP) kinase and cyclooxygenase-2 (COX-2), protein kinase C (PKC), respectively. In contrast, a c-Jun NH2-terminal kinase inhibitor increased the GR73632-evoked SP release. Conclusion These results indicate that the neurokinin-1 receptor activation by its agonists regulates the SP release process involving the activation of MAP kinases, PKCs and COX-2 from cultured DRG neurons.